Vaccination Of Village Chickens Against Newcastle Disease - Ideris, Aini (1989)

(untitled)
The village poultry is an important component of the poultry industry in South East Asia . However , Newcastle disease is always a thre at to them . While the disease is usually adequately control led by repeated applications of suitable vaccines in commercial poultry , it has not been success fully controlled in village chickens. A new method of vaccine production and administration for the village chickens needs to be developed . The objective of this study was to select an avirulent Newcastle disease virus which is immunogenic , heat resistant and transmissible among chickens and to incorporate the virus in feed that can be offered to chickens . The vaccine was prepared by coating an immunogenic and heat tolerant sub strain of V 4 virus onto food pellets . A nominal chicken do s e o f vaccine was 10 g of pellets containing 10650 % egg infectious doses of vaccine virus. The vaccine was prepared by coating an immunogenic and heat tolerant substrain of V 4 virus onto food pellets . A nominal chicken dose of vaccine was 10 g of pellets containing 10650 % egg infectious doses of vaccine virus.